Carbon adsorbents in oncology: achievements and perspectives - Nikolaev, V.G.; Sakhno, L.A.; Snezhkova, E.A.; Sarnatskaya, V.V.; Yushko, L.A. (Experimental Oncology, 2011)
The results of own investigations and literature data are summarized to determine the place of the main methods of adsorption therapy in complex treatment of the patients with malignant tumors. New possibilities for the usage of new generation of carbon adsorbents and modern adsorptive technologies in cancer treatment are discussed.